Labeling of Piperine with Iodine-131 as Radiotracer in the Development of Cancer Drugs from Indonesia’s Natural Products - Isti Daruwati; Yulia Anggraini; Aang Hanafiah Wangsaatmadja (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Piperine, as one of the secondary metabolites of pepper, shows many pharmacological activities in various studies, including as antiinflammatory, antimicrobial, hepatoprotective, antioxidant, and potentially anticancer agents. Cancer is still one of the leading causes of death in the world due to the absence of specific symptoms in early-stage of cancer. The development of drugs for early diagnosis and selective treatment of cancer cells is considered one of the best solutions to reduce mortality. The activity of piperine that could induce apoptosis of 4T1 breast cancer cells and HT-29 colon cancer cells at in vivo trials prove it as a potential compound that can carry radioactive atoms (as labeled-compound) to cancer cells. This study was conducted to determine the optimal conditions of labeling of piperine with iodine-131 in order to obtain a 131I-piperinewhich can later be used as a radiotracer in the development of cancer drugs. The labeling of piperine was performed by Chloramine-T iodination method and followed by purification with ion exchange chromatography. The optimal labeling results of piperine with 43.99% ± 1,23 radiochemical purity were obtained with piperine 3mg/300μL, chloramine-T 50 μg as an oxidizer, incubation time 30 min at room temperature, and 100 μg sodium metabisulphite as a reductor. To improve the purity of the preparation, purification by ion exchange chromatography method with Dowex 1x8 mesh 100-200 as resin was used until obtained 93,26% ± 0,94 of radiochemical purity. Further research is necessary before 131I-piperinecan be used as a radiotracer for cancer diagnosis in nuclear medicine.Keywords:cancer, iodine-131, 131I-piperine,labeled-compound, radiotracer